(NaNALIZ MUZYKALXNYH PROIZWEDENIJs (NTEOREQ(B.(Nu^EBNOE POSOBIEs - (NzADNEPROWSKAQ g(B. (Nw(B.s ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2022)
(Nw DANNOM POSOBIE PREDSTAWLENY OSNOWNYE FORMYEWROPEJSKOJ MUZYKI(B.s
Keywords: (NtEORIQ(B.s